Hygienic Assessment Of The Class Of Working Conditions According To The Chemical Factor In The Production Of Polyethylene Products (Texas Journal of Medical Science, 2024)
This article contains a class of working conditions according to sanitary rules and regulations No. 0141-03 “The severity and intensity of the labor process in a production environment, hygienic classification of indicators of harmfulness and danger of working conditions” and the determination of the summation coefficient.